2011
DOI: 10.1136/bjsm.2011.084038.180
|View full text |Cite
|
Sign up to set email alerts
|

Functional movement screen: inter-rater and subject reliability

Abstract: Background A screening test evaluates a functional movement by assessing an athlete's functional limitations, weaknesses, or impairments that may increase the risk of injury for the athlete. Objective To assess the inter-rater reliability and subject variability of the Functional Movement Screen (FMS) and to analyze the use of video scoring as opposed to live scoring. Design A reliability study. Each athlete was tested and retested, 1 week apart by the same rater, who also scored the athlete's fi rst session f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 0 publications
0
9
0
Order By: Relevance
“…Currently several previous reliability studies for the FMS TM using the standard scoring system have been published [21][22][23][24][25][26]. Overall, inter-rater reliability ranged from poor (k a = 0.38 [23]), throughout good (ICC = 0.87 and ICC = 0.89 [22]) to high (ICC = 0.92 [24] and k w = 0.98 [24]), depending on the performed statistical analysis. For intra-rater reliability intra-class correlation coeffi-cients was good and ranged from ICC = 0.6 [23] to ICC = 0.946, respectively to the experience level [26].…”
Section: Assessment Of the Level Of Fundamental Movement Skillsmentioning
confidence: 99%
See 2 more Smart Citations
“…Currently several previous reliability studies for the FMS TM using the standard scoring system have been published [21][22][23][24][25][26]. Overall, inter-rater reliability ranged from poor (k a = 0.38 [23]), throughout good (ICC = 0.87 and ICC = 0.89 [22]) to high (ICC = 0.92 [24] and k w = 0.98 [24]), depending on the performed statistical analysis. For intra-rater reliability intra-class correlation coeffi-cients was good and ranged from ICC = 0.6 [23] to ICC = 0.946, respectively to the experience level [26].…”
Section: Assessment Of the Level Of Fundamental Movement Skillsmentioning
confidence: 99%
“…Overall, inter-rater reliability ranged from poor (k a = 0.38 [23]), throughout good (ICC = 0.87 and ICC = 0.89 [22]) to high (ICC = 0.92 [24] and k w = 0.98 [24]), depending on the performed statistical analysis. For intra-rater reliability intra-class correlation coeffi-cients was good and ranged from ICC = 0.6 [23] to ICC = 0.946, respectively to the experience level [26]. Moreover, normative values for in a young, active population were established [27].…”
Section: Assessment Of the Level Of Fundamental Movement Skillsmentioning
confidence: 99%
See 1 more Smart Citation
“…Only one study found the inter-rater reliability to be poor (Shultz et al, 2011). In those studies that investigated intra-rater / test-retest reliability of the FMS it was found to range from good (Shultz et al, 2011;Teyhen et al, 2012) to excellent (Onate et al, 2012).…”
Section: Functional Movement Screen (Fms) Reliabilitymentioning
confidence: 99%
“…In this literature review eleven studies were identified that investigated the reliability of different functional movement screening tools (Table 2.3); nine looked specifically at the inter-rater, intra-rater and/or test-retest reliability (Butler, Plisky, & Kiesel, 2012;Frohm et al, 2012;Minick et al, 2010;Onate, Cortes, Welch, & van Lunen, 2010;Onate et al, 2012;Padua et al, 2009;Schneiders et al, 2011;Shultz et al, 2011;Teyhen et al, 2012). One investigated reliability as part of a pilot study imbedded within a correlation study (Smith et al, 2012), and one as part of a thesis into the development, reliability and effectiveness of a screening tool (Kritz, 2012).…”
Section: Functional Movement Screening Tools Reliability 233mentioning
confidence: 99%